Operationalizing Constructs for Measuring Sustainable Competitive Advantage - Chishamba, Jealous (Acta Universitatis Danubius. Œconomica, 2024)
This paper examines the challenges of operationalizing and measuring sustainable competitive advantage (SCA) in organizations, emphasizing the need to integrate both financial and non-financial dimensions for a comprehensive understanding of SCA. Building on competitive strategy theories such as the Resource-Based View (RBV), Dynamic Capabilities View (DCV), Structural Approach, and Blue Ocean Strategy (BOS), this paper synthesizes these frameworks to recommend practical operational constructs for measuring SCA, while addressing gaps in aligning and applying these theories consistently in SCA measurement. A semi-systematic and integrative literature review identified five key constructs essential for measuring SCA: effective supply chain management, product differentiation and innovation, organizational responsiveness, cost leadership, and persistence of financial indicators. The findings reveal that while these constructs are critical, their operationalization is complex and context-dependent, particularly in adapting to market shifts and technological advancements. Longitudinal studies are recommended to further explore their effectiveness in capturing the dynamic nature of SCA. This study provides valuable insights for academics, practitioners, and strategic leaders on how these constructs can guide strategic decision-making and resource allocation in competitive environments, enabling organizations to maintain long-term success. The paper contributes to the literature by offering a comprehensive framework for operationalizing SCA, highlighting key constructs and their practical implications. The study provides a foundation for future research and offers actionable insights for navigating today’s rapidly evolving business landscape.